2018
DOI: 10.5539/gjhs.v11n1p155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Nutrients and Microbiological Characteristics of the Indonesian Dadih As a Food Supplementation

Abstract: Dadih, an Indonesia traditional fermented buffalo milk, is produced and consumed by the West Sumatra Minangkabau ethnic group of Indonesia that considered beneficial for human health. The objective of this study was to know nutrients composition and bacteriology characteristics of dadih that collected from Tanah Datar and Agam districs in West Sumatera province, Indonesia. This study initiated with analysis of biochemical of dadih covering protein, lipid, moisture value, ash content, pH, and titritable acidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Based on the previous research by Helmizar et al (2019), protein in dadih is estimated to approximately 12.41% and 49.64 g of protein per 100 g of dadih. This means that dadih does not have a sufficient amount of protein to fulfill the nutritional need for pregnant mothers who need a protein intake of 77 g/day (Indonesian Recommended Daily Intake, 2013).…”
Section: Analysis Of Amino Acidmentioning
confidence: 96%
“…Based on the previous research by Helmizar et al (2019), protein in dadih is estimated to approximately 12.41% and 49.64 g of protein per 100 g of dadih. This means that dadih does not have a sufficient amount of protein to fulfill the nutritional need for pregnant mothers who need a protein intake of 77 g/day (Indonesian Recommended Daily Intake, 2013).…”
Section: Analysis Of Amino Acidmentioning
confidence: 96%
“…For example, the pH and total acidity of dadih varied between regions. Helmizar et al [9] reported that the type of buffalo feed may impact the pH and acidity of dadih. As an example, the grass (Imperata cylindrica) in Agam, and banto grass (Leersia hexandra Sw.) with rice straws in Tanah Datar were used to feed the buffaloes.…”
Section: Nutritional Value and Chemical Analysis Of Dadihmentioning
confidence: 99%
“…Furthermore, the different types of bamboo (each type has different thickness, porosity, and other characteristics) used to produce dadih and the addition of food supplements given to the buffaloes in different regions may also affect the chemical composition of dadih, such as protein, fat, water content, etc. [9]. The uncontrolled production that causes different chemical compositions of dadih in different regions leads to the idea of production standardization, which is described in Section 9.…”
Section: Nutritional Value and Chemical Analysis Of Dadihmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the manufacturing of Dadiah is still in a traditional process and has not met any national standards [17] or international standards [18] for yogurt and fermented milk, Dadiah provides safety and health for people who consume it. There are no pathogenic bacteria in Dadiah [19]. Several studies had demonstrated that Dadiah had beneficial effects on the intestinal health of mothers and children due to its nutritional value and its role as a probiotic [19], [20], [21], [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%